Maintaining informatics training learning outcomes with a COVID-19 era shift to a fully online flipped course - Heather T.D. Maness; Hesamedin Hakimjavadi; Srikar Chamala (Elsevier, 2023)
The emergence of the coronavirus disease 2019 pandemic forced us to adapt our recently developed informatics training serving a variety of students as well as faculty and staff. The successful flipped classroom course series (a hybrid-format with both asynchronous online learning and in-person synchronous components) was shifted to a fully online format with the synchronous portion now held via web-based video conference. We repeated our participant survey at the end of each of the 3 one-credit courses to compare student satisfaction and learning outcomes achievement to the original offering. The responses were overall very positive again with a slight response distribution improvement in some measures of satisfaction. Likewise, students reported similar achievement of the learning outcomes across all courses with some Unix coourse objectives receiving higher competency agreement in the new, fully online version. Overall, the fully online version of the course series was equally successful, if not more so, than the original version with a physical classroom session each week. Given that participants also had strong agreement with a new question that they would prefer online class meetings instead of in a classroom, even if there wasn't a global pandemic (citing a variety of logistical reasons such as "convenience of screen sharing," parking issues, and job-related time constraints), the fully online version of the informatics training will be retained.